2024
DOI: 10.3389/fimmu.2024.1372959
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomic analyses reveal diverse and dynamic changes of distinct populations of lung interstitial macrophages in hypoxia-induced pulmonary hypertension

Sushil Kumar,
Claudia Mickael,
Rahul Kumar
et al.

Abstract: IntroductionHypoxia is a common pathological driver contributing to various forms of pulmonary vascular diseases leading to pulmonary hypertension (PH). Pulmonary interstitial macrophages (IMs) play pivotal roles in immune and vascular dysfunction, leading to inflammation, abnormal remodeling, and fibrosis in PH. However, IMs’ response to hypoxia and their role in PH progression remain largely unknown. We utilized a murine model of hypoxia-induced PH to investigate the repertoire and functional profiles of IMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Despite these differences, both hypoxia and Schistosoma cause experimental and human PH. Work in the hypoxia PH system identified 4 IM subpopulations, characterized as MHCII hi CCR2 + EAR2 + , TLF + VCAM1 hi , MHCII hi CCR2 + EAR2 - , and TLF + VCAM1 lo ( 21 ). Comparing these 4 IM subpopulations in hypoxic-PH to the 3 populations in Schistosoma -PH identified that the Schistosoma -PH CCR2 + IMs were analogous to the hypoxia-PH MHCII hi CCR2 + EAR + IMs; the Schistosoma -PH MHCII hi IMs were analogous to the hypoxia-PH MHCII hi CCR2 + EAR - IMs; and the Schistosoma -PH FOLR2 + IMs were analogous to a combination of the TLF + VCAM hi and TLF + VCAM lo IMs in the hypoxia-PH model ( Supplementary Figure S19 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite these differences, both hypoxia and Schistosoma cause experimental and human PH. Work in the hypoxia PH system identified 4 IM subpopulations, characterized as MHCII hi CCR2 + EAR2 + , TLF + VCAM1 hi , MHCII hi CCR2 + EAR2 - , and TLF + VCAM1 lo ( 21 ). Comparing these 4 IM subpopulations in hypoxic-PH to the 3 populations in Schistosoma -PH identified that the Schistosoma -PH CCR2 + IMs were analogous to the hypoxia-PH MHCII hi CCR2 + EAR + IMs; the Schistosoma -PH MHCII hi IMs were analogous to the hypoxia-PH MHCII hi CCR2 + EAR - IMs; and the Schistosoma -PH FOLR2 + IMs were analogous to a combination of the TLF + VCAM hi and TLF + VCAM lo IMs in the hypoxia-PH model ( Supplementary Figure S19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pathologic mechanisms of monocyte recruitment and IMs are also present in hypoxia-induced PH ( 3 , 7 , 25 29 ). There is a high degree of similarity in the IM populations observed in both hypoxic- and Schistosoma-PH ( 21 ), although hypoxia induces a Type 1 inflammatory phenotype in IMs whereas Schistosoma induces a Type 2 inflammatory phenotype. scRNAseq analysis of the hypoxia-PH model revealed 2 IM subpopulations directly analogous to the CCR2+ and MHCII hi IM subpopulations in Schistosoma-PH ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations